Chapter Democracy under the kothornos: Thucydides and Xenophon on Theramenes - Sano, Lucia (Studi e saggi, 2022)
We analyze the political actions of Theramenes as described by Thucydides (during the coup of 411 BCE) and Xenophon (under the Thirty, 404-403 BCE) to map the features that converged to make him a paradigmatic character in the ancient Greek political imaginary. Xenophon, at least, may have been an eyewitness to the facts reported and both historians have conditioned Theramenes' portrayal by later authors. We highlight the traits of Theramenes that fostered his identification as either the quintessence of the turncoat or as a role-model for moderate politics. Our goal is also to discuss the implications of his political stances for the configuration of Athenian democracy in the last quarter of the 5th century and how this may still help us consider our own democratic system and its flaws.